WORK LIFE BALANCE OF WHITE COLLAR EMPLOYEES IN A MULTINATIONAL COMPANY AND A JOINT VENTURE IN BANGLADESH - Afroze, Rawnak (PEOPLE: International Journal of Social Sciences, 2019)
This paper is based on Work Life Balance (WLB) in a Multinational corporation (MNC) and a Joint venture (JV) in Bangladesh. It focuses on the extent to which companies have implemented WLB policies for their executive employees, and the factors that inhibit and enhance these organizations’ ability to implement WLB. The literature on WLB discourse has shown that WLB is still at its infancy in Bangladesh. Provision of WLB policies is relatively neglected in organizations in Bangladesh as compared to the other advanced countries. However, MNCs and JVs from developed economies are playing a crucial role in transferring best practices to their operations in developing countries. Therefore, a MNC and a JV were selected to pursue this research. The MNC was chosen from retailing and the JV from telecommunication, as these sectors are exposed to foreign business and currently, they make the most significant contribution towards GDP.The research used semi-structured interviews and the findings showed that WLB provisions are unsatisfactory in foreign companies in Bangladesh, although respondents’ reports showed that they are better than the Bangladeshi local companies. These foreign companies claim that there is hardly any scope for introducing extensive WLB policies in the Bangladeshi operations. They are more likely to adopt the local practices than the practices of their parent companies. Due to widespread job insecurity, employees are concerned about maintaining their jobs, and they do not believe in demanding WLB. The only factors, which may contribute favorably towards the employees’ WLB, are managerial support, good job autonomy and friendly working environment.